PERSEPSI DAN EFEKTIVITAS PELAKU UMKM TERHADAP PEMBERIAN BANTUAN SOSIAL PADA MASA PANDEMI COVID-19 DI KECAMATAN SERIRIT : (STUDI KASUS DESA SULANYAH) - Suardika, I Ketut; Kadek Angga Kurniawan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
The COVID-19 pandemic is an epidemic that has spread to various continents and countries. Since March 2nd, 2020, the name Indonesia has been included in the country affected by the corona virus. Not only is it detrimental on the health side, this pandemic has greatly impacted the economy in Indonesia, especially in Seririt District, especially in Sulanyah Village, most of the people who are involved in the business sector, one of which is through micro, small and medium enterprises, suffered losses. In this case, it is hoped that the role of the government will participate in helping the development of these micro, small and medium enterprises. One of the government programs to assist business actors is by providing social assistance through the micro, small and medium enterprises Direct Cash Assistance program in the form of Micro Business Productive Assistance. This type of research is a qualitative research that seeks to collect facts and circumstances properly through interviews. The interviews conducted in this study were intended for business actors affected by Covid-19 and recipients of assistance. The results of the research show that the effectiveness of assistance provided by the government is very helpful in maintaining and developing businesses for beneficiaries. With this assistance, sales turnover, goods production, and business actors' profits have increased.